Financial strategy in the context of building a competitive business strategy in today’s market. (Economics and region, 2018)
The features of the financial strategy in constructing a competitive business strategy in today's market. The process of strategic management and its stages. The basic stages of the financial strategy of the enterprise as one of the most important elements of competitive strategy. Development of an effective financial strategy is a priority management enterprise in modern conditions. This is due to the fact that the implementation of general corporate and functional strategies requires resource support, opportunities and ways to get the best of which can be set only in the financial strategy of the organization. The financial strategy that ensures balance available resources with the goals and objectives of the company, is one of the most important elements of competitive strategy. Development of financial strategy execution requires strategic analysis, financial planning and control, as well as an effective system of financial management. The purpose of the article is the disclosure of formulation and implementation of competitive strategy taking into account the financial strategy in the current market conditions.
Keywords: competitive strategy; financial strategy; competition; strategic planning